FACTORS AFFECTING CONSUMER BEHAVIOR ON iPhone PURCHASE DECISIONS (Case Study on Indonesian Christian University Students) - Manalu , Meilan Alvionita; Tobing , Fenny BNL. (Fundamental Management Journal, 2022)
This study aims to determine the effect of lifestyle, product quality and price on iPhone purchasing decisions on iPhone users at the Christian University of Indonesia. iPhone is a smartphone product from the company apple.inc, and one of the smartphone brands that is booming in all circles. The data analysis method used is multiple linear analysis, classical assumption test, F test, t test, coefficient of determination. In this study, the population used in this study were all Indonesian Christian University students who use iPhone, with a sample of 100 respondents. The results of this study indicate that lifestyle, product quality and price simultaneously affect iPhone purchasing decisions. This is indicated by 0.000< 0.05 and the value of Fcount 29,481 > Ftable 2,70.Keywords: Lifestyle, Product Quality, Price, Purchase Decision.